Reversible single crystal-to-single crystal double [2+2] cycloaddition induces multifunctional photo-mechano-electrochemical properties in framework materials - Sherman, Dylan A.; Murase, Ryuichi; Duyker, Samuel G.; Gu, Qinyi; Lewis, William; Lu, Teng; Liu, Yun; D’Alessandro, Deanna M. (Nature communications, 2020)
Reversible structural transformations of porous coordination frameworks in response to external stimuli such as light, electrical potential, guest inclusion or pressure, amongst others, have been the subject of intense interest for applications in sensing, switching and molecular separations. Here we report a coordination framework based on an electroactive tetrathiafulvalene exhibiting a reversible single crystal-to-single crystal double [2 + 2] photocyclisation, leading to profound differences in the electrochemical, optical and mechanical properties of the material upon light irradiation. Electrochemical and in situ spectroelectrochemical measurements, in combination with in situ light-irradiated Raman spectroscopy and atomic force microscopy, revealed the variable mechanical properties of the framework that were supported using Density Functional Theory calculations. The reversible structural transformation points towards a plethora of potential applications for coordination frameworks in photo-mechanical and photoelectrochemical devices, such as light-driven actuators and photo-valves for targeted drug delivery. Porous coordination frameworks that undergo reversible structural transformations are promising for sensing, switching and separations. Here, the authors report an electroactive framework that exhibits a reversible single crystal-to-single crystal double [2+2] photocyclisation, leading to property changes.